Knowledge, Attitude and Practice on Oral Health among Patients Visiting Dental Center: A Cross-Sectional Study - Chaulagain, Tekendra; Khan, Sajjad Ahmed; Koirala, Pramila; Upreti, Amit; Chaudhary, Roshan Kumar; Bhatta, Nikita (Nepal Journal of Health Sciences, 2025)
Introduction: Oral health is a vital component of overall health and quality of life. Poor knowledge, negative attitudes, and inadequate practices regarding oral hygiene contribute significantly to the global burden of dental diseases, especially in low- and middle-income countries.Objective: To assess the knowledge, attitude, and practice of oral health among patients attending a dental centre in Nepal.Methods: A cross-sectional study was conducted among 353 patients attending a dental centre. Data were collected using a structured questionnaire covering socio-demographic characteristics, oral health knowledge, attitude, and practices. Descriptive statistics, chi-square tests, and logistic regression were applied to assess associations between socio-demographic variables and knowledge, attitude, and practice outcomes.Results: The mean age of participants was 36.65 ± 15.88 years, with almost equal gender distribution. Overall, participant’s demonstrated good knowledge of oral health, with 92.1% recognizing the importance of brushing twice daily, 88.1% acknowledging the harmful effect of sugary foods, and 76.8% aware of the impact of dental diseases on general health. Attitudes were generally positive, with 85.8% agreeing that oral health is as important as general health, and 91.8% recognizing the harms of tobacco and alcohol.Conclusion: The study highlights generally good knowledge and positive attitudes toward oral health, but suboptimal practices persist, particularly regarding toothbrush replacement and frequency of brushing. Targeted health education and behavioral interventions are recommended to bridge the gap between knowledge and practice for improved oral health outcomes.